Perumusan Strategi Promosi Desa Wisata Daiama sebagai Upaya Meningkatkan Kunjungan Wisatawan di Kabupaten Rote Ndao - I Wayan Adi Putra Ariawan; Daniel Pandu Mau; Anak Agung Ngurah Sedana Putra; Rizal Kurniansah (PT. PENERBIT TIGA MUTIARA, 2026)
Daiama Tourism Village in Rote Ndao Regency possesses significant natural and cultural tourism potential; however, its tourism promotion remains suboptimal, resulting in fluctuating tourist visitation rates. This study aims to analyze promotional activities, identify factors influencing promotional effectiveness, and formulate promotional strategies to increase tourist visits. The research employed a qualitative descriptive method through observation, interviews, literature review, and documentation, supported by interactive data analysis and triangulation techniques. The findings reveal that promotional efforts still rely primarily on annual festivals and direct interpersonal communication without systematic support from planned digital media. This condition has contributed to fluctuations in tourist arrivals, increasing from 587 visitors in 2022 to 711 visitors in 2023, before declining to 503 visitors in 2024 and 468 visitors in 2025. Constraining factors include limited human resources, weak digital media management, and the underdeveloped institutional capacity of the Tourism Awareness Group (Pokdarwis). The study concludes that promotional strategies should be directed toward digital marketing, strengthening cultural identity and local storytelling, as well as enhancing community and institutional capacity. The novelty of this study lies in the development of a sustainable promotional model that integrates digital marketing, cultural storytelling, community participation, and the strengthening of Pokdarwis institutions in accordance with the characteristics of Daiama Tourism Village as a nature- and culture-based tourism destination.